2011
DOI: 10.7202/045829ar
|View full text |Cite
|
Sign up to set email alerts
|

Approche spatialisée dans la modélisation hydrogéologique d’un ancien secteur minier

Abstract: La présente recherche concerne l’étude d’un site situé dans le nord-est de la France dont le régime hydrogéologique est perturbé par la présence des galeries d’une ancienne mine de fer. Ce site a fait l’objet d’une modélisation hydrodynamique en trois dimensions. Quatre couches représentant le système aquifère et les formations imperméables sont numérisées; le réseau de galeries est représenté de manière explicite dans la couche ferrifère au moyen d’une option du code MARTHE qui intègre la géométrie des galeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…This results in a heterogeneous sedimentary formation with an average thickness of 330 m (Calvet et al, 2021) widely observed in all interfluves of southwestern France (Hubschman, 1975). The clayey and calcareous composition of these sediments results in an overall low hydraulic conductivity around 10 −9 m/s, like in similar facies sedimentary deposits, such as the Toarcian marls (Lucas & Vaute, 2011). Such a low hydraulic conductivity promoted waterlogging and hydric erosion, predominantly during the successive Quaternary glaciations (Meyer & Guillet, 1980;Revel & Bourgeat, 1981).…”
Section: Core Ideasmentioning
confidence: 99%
“…This results in a heterogeneous sedimentary formation with an average thickness of 330 m (Calvet et al, 2021) widely observed in all interfluves of southwestern France (Hubschman, 1975). The clayey and calcareous composition of these sediments results in an overall low hydraulic conductivity around 10 −9 m/s, like in similar facies sedimentary deposits, such as the Toarcian marls (Lucas & Vaute, 2011). Such a low hydraulic conductivity promoted waterlogging and hydric erosion, predominantly during the successive Quaternary glaciations (Meyer & Guillet, 1980;Revel & Bourgeat, 1981).…”
Section: Core Ideasmentioning
confidence: 99%